PHILOSOPHICAL PSYCHOLOGY DUALISM RATIONALISM DOGMATISM EMPIRICISM - RIEO, G MANUEL; BALDWIN, JAMES MARK (Departamento de Salubridad Publica, CD MEXICO, DF, MEX, 1913)
chapter- Discusses dualism from the perspectives of rationalism, dogmatism, empiricism, and occasionalism The movement traced in this chapter--from Descartes to Wolff--shows the development of one of the great motives of reflection: that which exhibits,
Keywords: PHILOSOPHICAL PSYCHOLOGY, DUALISM, RATIONALISM, DOGMATISM, EMPIRICISM; FILOSOFIA; FILOSOFIA DEL CONOCIMIENTO